Association of improvements in squat jump with improvements in countermovement jump without and with arm swing - Kukic, F. (Serbian Journal of Sports Sciences, 2020)
This study investigated the effects of an eight-week pre-season on-court volleyball along with strength and conditioning program on performance in squat jump (SJ) and countermovement jump without (CMJ) and with arm swing (CMJa); and whether the improvements in SJ contributed to improvements in CMJ and CMJa. Thirteen competitive female volleyball players completed an eight-week pre-season training program and their SJ, CMJ, and CMJa were assessed at the beginning and at the end of this period. Paired sample`s t-test calculated the differences between two tests, while regression analysis investigated if an improvement or reduction in SJ was associated to improvements or reductions attained in CMJ and CMJa. In general, applied training significantly improved (p<0.01) SJ (10.2%), CMJ (10.2%), and CMJa (6.9%), with an exception to a few cases. Changes in SJ were moderately associated with changes in CMJ (R2=0.536, p=0.005) and CMJa (R2=0.357, p=0.020). On-court volleyball training followed by a strength and conditioning program significantly improved jumping performance, whereby contractile strength characteristics explained moderate amounts of improvement in CMJ and CMJa, which are the most common jumps in volleyball games. Analyzing to what degree certain elements explain components of performance such as ability to jump vertically adds to the precision of planning and reduces the possibility of error.